Evaluation of pharmacist's practices regarding the antimicrobials dispensing: a simulated patient study - Elindayane Vieira de Souza; Lara Joana Santos Caxico Vieira; Sylmara Nayara Pereira dos Santos; Sabrina Cerqueira-Santos; Kérilin Stancine Santos Rocha; Rafaella de Oliveira Santos Silva; Divaldo Pereira de Lyra Jr (BMC, 2022)
Abstract Background The indiscriminate use of antimicrobials is considered a major contributing factor to the increase in antimicrobial resistance. Community pharmacies are the main source of access to antimicrobials, and pharmacists are in a strategic position to promote rational use of these medicines. Therefore, it is important to know dispensing service quality. Objective To evaluate the behavior of pharmacists in dispensing antimicrobials in community pharmacies in northeast Brazil. Methods This cross-sectional pilot study was conducted from August to October 2021 in a private community pharmacy chain in Sergipe. Dispensing was evaluated using the simulated patient (SP) technique. Two SP asked the pharmacists for the antimicrobials (case clinic 1: upper respiratory infection; case clinic 2: urinary tract infection) and recorded the service through audio. Dispensing practices were independently analyzed by two researchers based on the tools available in the literature. Data were presented using descriptive statistics. Results A total of 54 simulated patient visits were conducted. Based on the 12 steps recommended by the research team for good dispensing, pharmacists asked an average of 1 (±1.17) question for upper respiratory infections and 0.3 (±0.54) for urinary tract infections, as well as provided counseling (mean number of recommendations, 2.6 (±1.44) and 4.5 (±2.35), respectively). As for communication skills, pharmacists had a regular score (3.07 ± 0.34). Furthermore, there was no significant difference in the number of steps and counseling recommendations by pharmacists in dispensing clinical cases 1 and 2 (p = 0.0674). Conclusion The quality of antimicrobial dispensing was evaluated as suboptimal, requiring improvements in practice and multifaceted strategies to promote continuing education of these professionals. In addition, awareness actions for the population must be implemented to promote the rational use of antimicrobials and reduce microbial resistance.